EMOTIONAL PROCESSION OF ARTICLES CONTENTS IN THE MACEDONIAN MEDIA - Serafimovska, Eleonora; Markovikj Marijana (Institute for Sociological, Political and Juridical Research, 2015)
Macedonia will remember 2015 as a year of long term political crisis. It was a year of intensive activity against the actual Government. There were “opposition bombs”, disclosed incriminating phone calls, strikes in education, mass protests, camping in front of the Government and the Parliament, police action against terrorist in Kumanovo, migrant crisis .... The understanding of the start and the end points of the crisis largely depend on individual perception created as a result of personal experience and experience mediated through offline networks, online networks and media. Beside diversity of the events in surrounding there is also a difference in style of processing or living own emotions (feeling them, expressing them, understanding them). This research focusses on how students process emotions provoked by news /media stories on the events connected to the above mentioned critical political events. Students from Faculty of Philosophy, University “Ss. Cyril and Methodius” voluntary accepted to take part in this research. Two research instruments were used: questioner for the evaluation of the media content and their influence on respondent’s emotions and Emotional Processing Scale (EPS) for nature of processing emotions. The research design provides quantitative and qualitative analysis. This study showed that anger, fear and rage are dominantly provoked by negative emotions which are unprocessed or there is avoidance of coping with them (the two unhealthy ways of emotional processing).
Keywords: Emotional processing, Media and emotions, Media stress, Emotional processing scale